Use of technology, information, communication and virtual classroom teaching course in the Health Management education for medical residents of the Faculty of Medicine, Universidad Nacional Mayor de San Marcos, 2015 - Matzumura, Juan P. (2016)
Introduction. Since 2005 the Faculty of Medicine of the Universidad Nacional de San Marcos incorporated a competency-based training in the various curricula of medical training programs, including seven skills required by medical residents. The management and administration subjects were some of those skills that seemed to receive less development and attention. Objective. To describe and analyze the use of technology, information, communication and virtual classroom in the health management education. Design. Quantitative, descriptive, prospective and cross-sectional study. Setting. Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Participants. 91 medical residents enrolled in health management. Interventions. A non-probabilistic sample was selected by convenience. An open source virtual classroom was implemented. The reliability index of the instrument was to 0.93. The questionnaire was applied in online mode. Results. The main source of acquiring knowledge and skills were on their own; 83.9% would recommend the implementation and use of the virtual classroom for the development of other courses in the Second Specialization Program in Human Medicine. And 90% considered important to use the virtual classroom during their specialist training. Conclusions. The implementation of the virtual classroom and its usefulness for specialist medical training is considered.